Odpowiedź :
Zad1
1 5/9 : 14 = 14/9: 14/1 = 14/9 x 1/14 = 1/9 (skracasz 14 z 14; w liczniku zostaje 1 w mianowniku 9)
1/9 : 2 = 1/9 : 2/1 = 1/9 x 1/2 = 1/18
Zad 2
1,3 + 2,7 : 0,9 + 5/6 x (-3,6) = 1,3 + 3 + 5/6 x (-3 6/10) = 1/3 + 3 + 5/6 x (-36/10) (skracasz ułamki)= 1,3 +3 + (-6/2) = 1,3 + 3 + (-3) = 4,3 + (-3) = 4,3 - 3 = 1,3
3,9 x(iks) = 1,3
x = 1,3 : 3,9
x = 1 3/10: 3 9/10
x = 13/10 : 39/10
x = 13/10 x (razy) 10/39 (skracasz 10 z 10)
x = 13/39 (skracasz przez 13)
x = 1/3
Zad 3
-4,5 + (-1 1/3) + 3,75 = -4 5/10 - 1 1/3 + 3 75/100= - 4 15/30 - 1 10/30 + 3 75/100 = -5 25/30 + 3 75/100 = -5 250/300 + 3 225/300 = -2 25/300 = -2 1/12
Zad 4
[ -15 + (-25) : 5] : (6-10) = [-15 + (-5)] : (-4) = (-20) : (-4) = 5
Zad 5
240 : (-4) : (-12) : (-5) = (-60 ): (-12) : (-5) = 5 : (-5) = -1
Zad 6
- (2,4 * 5/24 - 4/5) : (-0,125) + 4 = - (2 4/10 x 5/24 - 4/5) : (-0,125) + 4 = - (24/10 * 5/24 - 4/5) : (-0,125) + 4 = -(1/5 - 4/5) : (-0,125) + 4 = - (-3/5) : (-0,125) + 4 = 3/5 : (-0,125) + 4 = 0,6 : (-0,125) + 4 = -4,8 + 4 = -0,8
1 5/9 : 14 = 14/9: 14/1 = 14/9 x 1/14 = 1/9 (skracasz 14 z 14; w liczniku zostaje 1 w mianowniku 9)
1/9 : 2 = 1/9 : 2/1 = 1/9 x 1/2 = 1/18
Zad 2
1,3 + 2,7 : 0,9 + 5/6 x (-3,6) = 1,3 + 3 + 5/6 x (-3 6/10) = 1/3 + 3 + 5/6 x (-36/10) (skracasz ułamki)= 1,3 +3 + (-6/2) = 1,3 + 3 + (-3) = 4,3 + (-3) = 4,3 - 3 = 1,3
3,9 x(iks) = 1,3
x = 1,3 : 3,9
x = 1 3/10: 3 9/10
x = 13/10 : 39/10
x = 13/10 x (razy) 10/39 (skracasz 10 z 10)
x = 13/39 (skracasz przez 13)
x = 1/3
Zad 3
-4,5 + (-1 1/3) + 3,75 = -4 5/10 - 1 1/3 + 3 75/100= - 4 15/30 - 1 10/30 + 3 75/100 = -5 25/30 + 3 75/100 = -5 250/300 + 3 225/300 = -2 25/300 = -2 1/12
Zad 4
[ -15 + (-25) : 5] : (6-10) = [-15 + (-5)] : (-4) = (-20) : (-4) = 5
Zad 5
240 : (-4) : (-12) : (-5) = (-60 ): (-12) : (-5) = 5 : (-5) = -1
Zad 6
- (2,4 * 5/24 - 4/5) : (-0,125) + 4 = - (2 4/10 x 5/24 - 4/5) : (-0,125) + 4 = - (24/10 * 5/24 - 4/5) : (-0,125) + 4 = -(1/5 - 4/5) : (-0,125) + 4 = - (-3/5) : (-0,125) + 4 = 3/5 : (-0,125) + 4 = 0,6 : (-0,125) + 4 = -4,8 + 4 = -0,8
Zad1
[1 5/9 : 14 ]:2=
= [14/9: 14/1]:2 =
= [14/9 x 1/14]:2 =
=1/9: 2=1/9 : 2/1 =
=1/9 x 1/2 = 1/18
Zad 2
1,3 + 2,7 : 0,9 + 5/6 x (-3,6) =
=1,3 + 3 + 5/6 x (-36/10) =
=1,3 +3 -6/2 =
= 1,3 + 3 -3 =
= 1,3
3,9 x = 1,3
x = 1,3 : 3,9
x = 1 3/10: 39/10
x = 13/10 : 39/10
x = 13/10 * 10/39
x = 13/39 = 1/3
Zad 3
-4,5 + (-1i 1/3) + 3,75 =
= -4 i 5/10 - 1 i1/3 + 3i 75/100=
= - 4 i 15/30 - 1i 10/30 + 3 i3/4 =
=-5 i25/30 + 3i i3/4 =
=-2 i 1/12
Zad 4
[ -15 + (-25) : 5] : (6-10) = [-15 + (-5)] : (-4) = (-20) : (-4) = 5
Zad 5
240 : (-4) : (-12) : (-5) = (-60 ): (-12) : (-5) = 5 : (-5) = -1
Zad 6
- (2,4 * 5/24 - 4/5) : (-0,125) + 4 =
= - (2 4/10 x 5/24 - 4/5) : (-0,125) + 4 =
= - (24/10 * 5/24 - 4/5) : (-0,125) + 4 =
= -(1/5 - 4/5) : (-0,125) + 4 =
= - (-3/5) : (-0,125) + 4 =
=3/5 : (-0,125) + 4 =
=0,6 : (-0,125) + 4 =
= -4,8 + 4 =
=-0,8
[1 5/9 : 14 ]:2=
= [14/9: 14/1]:2 =
= [14/9 x 1/14]:2 =
=1/9: 2=1/9 : 2/1 =
=1/9 x 1/2 = 1/18
Zad 2
1,3 + 2,7 : 0,9 + 5/6 x (-3,6) =
=1,3 + 3 + 5/6 x (-36/10) =
=1,3 +3 -6/2 =
= 1,3 + 3 -3 =
= 1,3
3,9 x = 1,3
x = 1,3 : 3,9
x = 1 3/10: 39/10
x = 13/10 : 39/10
x = 13/10 * 10/39
x = 13/39 = 1/3
Zad 3
-4,5 + (-1i 1/3) + 3,75 =
= -4 i 5/10 - 1 i1/3 + 3i 75/100=
= - 4 i 15/30 - 1i 10/30 + 3 i3/4 =
=-5 i25/30 + 3i i3/4 =
=-2 i 1/12
Zad 4
[ -15 + (-25) : 5] : (6-10) = [-15 + (-5)] : (-4) = (-20) : (-4) = 5
Zad 5
240 : (-4) : (-12) : (-5) = (-60 ): (-12) : (-5) = 5 : (-5) = -1
Zad 6
- (2,4 * 5/24 - 4/5) : (-0,125) + 4 =
= - (2 4/10 x 5/24 - 4/5) : (-0,125) + 4 =
= - (24/10 * 5/24 - 4/5) : (-0,125) + 4 =
= -(1/5 - 4/5) : (-0,125) + 4 =
= - (-3/5) : (-0,125) + 4 =
=3/5 : (-0,125) + 4 =
=0,6 : (-0,125) + 4 =
= -4,8 + 4 =
=-0,8
Zad1
[1 5/9 : 14 ]:2=
= [14/9: 14/1]:2 =
= [14/9 x 1/14]:2 =
=1/9: 2=1/9 : 2/1 =
=1/9 x 1/2 = 1/18
Zad 2
1,3 + 2,7 : 0,9 + 5/6 x (-3,6) =
=1,3 + 3 + 5/6 x (-36/10) =
=1,3 +3 -6/2 =
= 1,3 + 3 -3 =
= 1,3
3,9 x = 1,3
x = 1,3 : 3,9
x = 1 3/10: 39/10
x = 13/10 : 39/10
x = 13/10 * 10/39
x = 13/39 = 1/3
Zad 3
-4,5 + (-1i 1/3) + 3,75 =
= -4 i 5/10 - 1 i1/3 + 3i 75/100=
= - 4 i 15/30 - 1i 10/30 + 3 i3/4 =
=-5 i25/30 + 3i i3/4 =
=-2 i 1/12
Zad 4
[ -15 + (-25) : 5] : (6-10) = [-15 + (-5)] : (-4) = (-20) : (-4) = 5
Zad 5
240 : (-4) : (-12) : (-5) = (-60 ): (-12) : (-5) = 5 : (-5) = -1
Zad 6
- (2,4 * 5/24 - 4/5) : (-0,125) + 4 =
= - (2 4/10 x 5/24 - 4/5) : (-0,125) + 4 =
= - (24/10 * 5/24 - 4/5) : (-0,125) + 4 =
= -(1/5 - 4/5) : (-0,125) + 4 =
= - (-3/5) : (-0,125) + 4 =
=3/5 : (-0,125) + 4 =
=0,6 : (-0,125) + 4 =
= -4,8 + 4 =
=-0,8
[1 5/9 : 14 ]:2=
= [14/9: 14/1]:2 =
= [14/9 x 1/14]:2 =
=1/9: 2=1/9 : 2/1 =
=1/9 x 1/2 = 1/18
Zad 2
1,3 + 2,7 : 0,9 + 5/6 x (-3,6) =
=1,3 + 3 + 5/6 x (-36/10) =
=1,3 +3 -6/2 =
= 1,3 + 3 -3 =
= 1,3
3,9 x = 1,3
x = 1,3 : 3,9
x = 1 3/10: 39/10
x = 13/10 : 39/10
x = 13/10 * 10/39
x = 13/39 = 1/3
Zad 3
-4,5 + (-1i 1/3) + 3,75 =
= -4 i 5/10 - 1 i1/3 + 3i 75/100=
= - 4 i 15/30 - 1i 10/30 + 3 i3/4 =
=-5 i25/30 + 3i i3/4 =
=-2 i 1/12
Zad 4
[ -15 + (-25) : 5] : (6-10) = [-15 + (-5)] : (-4) = (-20) : (-4) = 5
Zad 5
240 : (-4) : (-12) : (-5) = (-60 ): (-12) : (-5) = 5 : (-5) = -1
Zad 6
- (2,4 * 5/24 - 4/5) : (-0,125) + 4 =
= - (2 4/10 x 5/24 - 4/5) : (-0,125) + 4 =
= - (24/10 * 5/24 - 4/5) : (-0,125) + 4 =
= -(1/5 - 4/5) : (-0,125) + 4 =
= - (-3/5) : (-0,125) + 4 =
=3/5 : (-0,125) + 4 =
=0,6 : (-0,125) + 4 =
= -4,8 + 4 =
=-0,8